Durability of Thermoplastic Polyurethane Round Belt Joint with Variations in Heating Methods and Cutting Shapes - Kusumo, Achmad Sabilarrosyad Prawiro; Murdani, Anggit (Universitas Negeri Malang, 2024)
Thermoplastic polyurethane round belts are widely used for conveyors in various industries, particularly in the food and beverage industry, due to their flexible and abrasion-resistant characteristics. These belts are also popular in manufacturing industries because of their ease of joint. However, a common issue arises when the conveyor belt breaks during the production process. This problem can be attributed to the lack of parameters in the belt joining process at companies. Operators do not have a standard parameter for the joining process. When there is an improper joining operation of an operator, the conveyor belt could fail earlier than the expected operation time. Therefore, the conveyor belt failure results in the loss of production time. This downtime can reach up to 15 minutes, i.e. the time required for the belt joining process. Previous studies have identified temperature and heating time as factors that influence the strength of the joint, especially when using a heating plate. Therefore, this research aims to determine the optimal parameters by varying the temperature and length of heating time in the joining process. Additionally, the research explored the impact of different cutting forms on the durability of the round belt joint. The results of this study indicate that the optimal temperature and heating time combination is 100°C for 3 seconds, resulting in a joint strength of 25,274 MPa. Furthermore, the triangular joint shape proved to be the most durable, with a record of 10,021 cycles.